PENERAPAN PENDEKATAN INKUIRI TERBIMBING UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV SD NEGERI 6 KADUR - Raudah Raudah; Zariul Antosa; Otang Kurniaman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This study was motivated by the low learning outcomes of IPS whose average grade is still at 67.50, while the final grade applied in grade IV of elementary school 6 Kadur is 65. This research is a classroom action research (CAR) consisting of two cycles, this research held in even semester 2016/2017. Subjects of this study amounted to 25 people. Out of 25 students, 11 people are completed and 14 are not yet completed. This study aims to improve the learning outcomes of IPS students of fourth grade elementary school 6 Kadur by applying the guided Inquiry learning approach. Guided Inquiry Learning approach is a learning approach that encourages students to discover the concepts or essence of learning. Instrument of this research consists of learning device and instrument of data collecting in the form of observation sheet and test question. The study was conducted from March 2016 to May 2017. The research data were analyzed by using MS. Excel including teacher activity data and student activity and improvement of student learning outcomes. Data analysis of teacher activity and student activity is based on observations made by the observer during the course of action. While the data analysis of student learning outcomes done after the implementation of daily test cycle I and cycle II. Based on the result of observation of teacher activity and student activity happened improvement as follows: teacher activity in cycle I only reach 70,83%, in cycle II increase become 91,67% while in student activity in cycle I only 66,67%, at cycle II increased to 95.83%. Analysis of student learning result data shows improvement as follows, improvement of mastery learning on base score only 11 people, in cycle II all student complete. Increased completeness caused by the increase in the average score of student learning outcomes from 65.20 in the initial score increased to 76.80 at the end of cycle II. This shows that the application of Inquiry learning approach can improve the learning result of IPS of fourth grade students of elementary school 6 Kadur.Keywords: Guided Inquiry Approach, IPS Study Results